How Biochar Affects Nitrogen Assimilation and Dynamics by Interacting Soil and Plant Enzymatic Activities: Quantitative Assessment of 2 Years Potted Study in a Rapeseed-Soil System - Khan, Zaid; Zhang, Kangkang; Khan, Mohammad Nauman; Bi, Junguo; Zhu, Kunmiao; Luo, Lijun; Hu, Liyong (Frontiers in Plant Science, 2022)
The amendment of biochar has been proposed to improve soil fertility and crop yield. However, consolidated information lacks explaining the role of biochar on soil and plant enzymatic activities involved in nutrients cycling in soil and accumulation in plants improving utilization of applied inorganic fertilizer and crop growth. In the current study, we evaluated the integral effects of biochar levels (B0:0, B15:15, B3:30 and B60:60 t ha-1) and nitrogen fertilizer levels (N0:0, N75:75, N225:225 and N450:450 kg ha-1) on soil physicochemical properties, enzymatic activities, nitrogen use efficiency (NUE) and grain yield of rapeseed for two years in the pots during 2020 and 2021. The findings revealed that compared to control (B0+N0), a combination of B30+N450 increased soil urease activity by 73% and 75%, and B60+N450 increased activities of soil catalase by 17% and 16%, and B60+N225 increased alkaline phosphatase by 17% and 19%, respectively in the first and second year. Moreover, a single application of high nitrogen at 450 kg ha-1 reduced the activities of plant nitrogen metabolism related enzymes, however; the integration of biochar at 30 t ha-1 compensated the high nitrogen toxicity and improved the activities of nitrate reductase (NR), nitrite reductase NIR, glutamate synthase (GS) and glutamine synthetase (GOGAT) at seedling stage (SS) and flowering stage (FS) in both years. The integration of biochar at 30 t ha-1 with nitrogen at 450 kg ha-1 induced synergetic effects on rapeseed growth through sorption of excessive nitrogen in soil and significantly improved the plant height up to 11% and 18%, pods plant-1 39% and 32% and grain yield plant-1 54% and 64%, respectively during the first and second year. Moreover, biochar at 15 t ha-1 along with nitrogen at 225 kg ha-1 resulted in the highest NUE of 29% in both years suggesting that biochar can also offset the deficiency of lower nitrogen. This study highlighted the ameliorative effect of biochar suppressing high nitrogen toxicity and lower nitrogen deficiency effects on rapeseed growth by improving nitrogen use efficiency via enhancing soil conditions, enzymatic activities and soil nitrogen utilization potential and thus improving rapeseed growth and yield.